"Small" prose of R. Gabudlkhakova: Features of the functioning of the brocade genre - Yuzmukhametova, Landysh N.; Amineva, Venera R.; Ibragimova, Leysan G.; Svetlova, Rosalia M.; Gulnara, Safina F. (Linguistics and Culture Review, 2021)
On the material of the works of R. Gabdulkhakova, the internal measure of the "small" genres of modern Tatar prose is revealed: in the brocade it is determined by the nature of the relationship of the narrative plot and its generalizing "ending." Genre varieties of brocade in the work of R. Gabdulhakova are described, which correspond to two directions of the plot movement: from external to internal or from single to universal and two types of narrative - from the 1st or from the 3rd person. It was concluded that the internal measure of the genre determines the nature of the relationship of the narrative plot and its generalizing "ending." Spatiotemporal relations and principles of organization of subject sphere characteristic of this genre are described.